ESTABLISH AN ADDITIVE (s;t)-FUNCTION IN EQUALITIES BY FIXED POINT METHOD AND DIRECT METHOD WITH n-VARIABLES IN BANACH SPACE - LYVANAN (IJRDO -JOURNAL OF MATHEMATICS, 2023)
In this paper we study to solve the of additive s, t -functional inequality with n-variables and their Hyers-Ulam stability. First are investigated in Banach spaces with a fixed point method and last are investigated in Banach spaces with a direct method.These are the main results of this paper.